Many-electron Electrochemical Processes Reactions in Molten Salts, Room-Temperature Ionic Liquids and Ionic Solutions - Andriiko, Aleksandr A.; Andriyko, Yuriy O.; Nauer, Gerhard E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Here, the authors provide a unified concept for understanding multi-electron processes in electrochemical systems such as molten salts, ionic liquids, or ionic solutions. A major advantage of this concept is its independence of assumptions like one-step many-electron transfers or ‘discrete’ discharge of complex species. Therefore this monograph is a unique resource for basic electrochemical research but also for many important applications such as electrodeposition, electrorefining, or electrowinning of polyvalent metals from molten salts and other ionic media.
Many-Electron Electrochemical Systems: Concepts and Definitions -- Many-electron Systems at Equilibrium -- Phenomenology of Electrochemical Kinetics -- Electrode Film Systems: Experimental Evidences -- Dynamics of a Non-Equilibrium Electrochemical System -- Electrochemistry of Ti(IV) in Ionic Liquids.
Keywords: Electrochemistry; Energy storage; Materials—Surfaces.; Thin films; Electrochemistry; Energy Storage; Surfaces and Interfaces, Thin Films